Politics as a transitory vocation: a case study of the post-parliamentary challenges experienced by former Victorian MPs. Issue 4 (2nd October 2022) - Nethery, Amy; Nwokora, Zim; Ferguson, Peter; Clarke, Matthew
ABSTRACT: A career in parliament is inherently a transitory vocation, and parliamentary turnover is critical for a healthy democracy. Yet many MPs fail to prepare for the time when they must leave parliament. This lack of preparedness exacerbates the challenges of post-parliamentary life. Drawing on research conducted with former members of the Parliament of Victoria, Australia, this article reports on the experiences of MPs leaving parliament. Former MPs, particularly those who leave the parliament involuntarily, experience serious challenges including a loss of identity, a fracturing of social relationships, and employment and financial stress. These outcomes may have democratic implications by discouraging highly capable candidates from diverse backgrounds from pursuing a career in parliament. Acknowledging that the role of modern parliaments is expanding well beyond their traditional purview, we offer practical recommendations to mitigate these issues.